FEMINISM IN THE MAIN CHARACTER OF THE MALEFICENT MOVIE BY ROBERT STROMBERT - Raudah Raudah; Ahmad Laut Hasibuan (PHILOLOGY Journal of English Language and Literature, 2026)
This research explores the portrayal of feminism in the main character of the movie Maleficent directed by Robert Stromberg. The study aims to analysis how the character Maleficent represents feminist values through her actions, decisions, and development throughout the film. Using a qualitative descriptive method, this research applies feminist literary criticism as the theoretical framework, particularly focusing on liberal feminism and radical feminism. The findings reveal that Maleficent’s character challenges traditional gender roles, reclaims her autonomy after betrayal, and transforms from a victim into a powerful, independent woman. The narrative presents Maleficent not only as a symbol of strength but also as a figure who redefines motherhood, love, and leadership from a feminist perspective. This study concludes that Maleficent offers a nuanced portrayal of female empowerment and contributes to contemporary feminist discourse in film.